PENILAIAN KEPARAHAN SERTA KOMORBIDITAS GANGGUAN PANIK - Sivanesh Tamilselvan (Intisari Sains Medis, 2015)
Background: Panic disorder with or without agoraphobia is a common anxiety disorders. Panic disorder patients who seek medical attention complaining of different emerging and many patients also suffer from anxiety disorders / other psychiatric or substance abuse disorders.Methods: This was a cross sectional study conducted using DSM IV TR criteria for panic disorder. Then patients with a diagnosis of panic disorder, panic disorder severity scale measured by 7 items (PDSS) to assess the severity of panic disorder. Clinically evaluated for the presence of agoraphobia or not. Special attention is given to check whether the patients had other comorbid psychiatric disorders.Results: The majority of patients 65% were women, 52.5% were in the age group 15-24 years and the mean age of patients was 23.82 years. The mean age of onset of symptoms of panic disorder was 21.3 years. The most frequent use of a substance is tobacco in 30% of patients. The most frequent comorbidities are major depressive disorder in 40% of patients. Agoraphobia was found in 24 (60%) patients. PA is the average duration of 22.37 minutes. 60% experienced moderate PD. The majority of the patterns of symptoms 67.5% of patients experienced symptoms of cardiovascular system (CVS).Conclusion: panic disorder often found in the age group 15-24 years. Symptoms often appear are the symptoms of a cardiovascular system that needs to be distinguished carefully. Needed attention to the high rates of comorbid substance use and psychiatric disorders in patients with panic disorder.